RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI MASJID BERBASIS WEB DI MASJID ASY-SYUHADA KOTA BATAM - sitorus, okta ainun; Silalahi, Mesri (LPPM Universitas Putera Batam, 2021)
Technology has a significant impact on everyday life, almost all activities use technology as a place to facilitate a work process. In the religious field, information technology can also be used by the community as a medium to obtain information and disseminate information about religion, one of which is in the mosque. The mosque itself has administrative processing which includes the preparation of an organizational structure, one of which is the Ash-syuhada Mosque in Batam. Based on the results of observations, the Ash-Syuhada Mosque does not yet have an information system in the management of mosque administration. Obstacles that are often faced in processing the cash of the Asy-syuhada mosque do not save time to look for administrative data, there is a difference in the calculation of incoming funds and expenditure funds, administrative processing is still complicated, the process of recording mosque cash data is not well organized, data processing of Ash-syuhada mosques. manual martyrs. For this reason, the author designed a WEB-based administrative information system intended for mosques to facilitate administrative processing.